P3_3 You really can’t boil the ocean - Smith, Kennedy; Bates, Ethan; Brewer, Lois; Sadler, Tommy (Physics Special Topics, 2022)
There is a well known phrase, “you can’t boil the ocean”, to describe an impossible task. This statement is technically a false statement given a large enough source of energy and enough time. However, is it really possible? In this paper we discuss and discover if you could feasibly boil any ocean in a reasonable time-frame given some assumptions. We discover that the energy required to boil the “easiest” ocean is 6 × 1024J, equivalent to the annual energy output of ∼ 4 × 107 times Canada’s T.C Energy Bruce nuclear generating stations [1].